POLITIK HUKUM UNDANG-UNDANG JAMINAN FIDUSIA DALAM MEWUJUDKAN KEPASTIAN HUKUM - rois, iwan (fakultas hukum universitas PGRI Semarang, 2018)
Â ABSTRACTProblems in this research: 1) Is the birth of Law No. 42 of 1999 on Fiduciary Guarantee has provided legal certainty for the parties? 2) What is the implementation and or implementation of Law Number 42 Year 1999 regarding Fiduciary Guarantee? A review of the legal certainty guaranteed to the parties and the implementation or implementation of Law Number 42 Year 1999 regarding Fiduciary Guarantee, carried out by normative juridical approach. The conclusion of this study is that to accommodate and respond to the wishes of the general public and especially the business world in order to achieve legal certainty and security of business, the government makes or issued Law No. 42 of 1999 on the Fiduciary Guaranty Act. Whereas with the enactment of Law No. 42 of 1999 the desired political law is a legal political model that provides a larger space for community participation, thereby creating a democratic character and creating a responsive legal configuration.Keywords: Political Law, Fiduciary Security, Legal Certainty.